Newly Discovered Letters of Władisław Syrokomla - Fedorowicz, Irena (Slavistica Vilnensis, 2015)
The article is devoted to the nine as-yet-unpublished letters by Władisław Syrokomla (Ludwik Kondratowicz, 1823–1862), kept at the Lithuanian State Historical Archive. Although some of the letters are undated, it can be assumed that they were written c. 1850–60. During that period Syrokomla lived at the Bareikiškės estate, 16 kilometers from Vilnius, and later moved to Vilnius, where he became well-known as a poet. Although this was one of his most-productive periods, both personally and professionally, he was unable to shield his large family from financial difficulties. The letters analyzed here show that despite having many debts, he attempted to help both his family members and acquaintances. The letters were addressed to four individuals: Syrokomla’s neighbor Władysław Fiorentin (4 letters), Ludwik Wrublewski (1), Rudolf Piesanka (3) and a certain Pavel (probably Kukolnik) (1). The letters to Wrublewski and Piesanka are business-related, the others are personal.